Projecting Age-Stratified Risk of Exposure to Inland Flooding and Wildfire Smoke in the United States under Two Climate Scenarios - Mills, David (Environ Health Perspect, 2018)
BACKGROUND: The public health community readily recognizes flooding and wildfires as climate-related health hazards, but few studies quantify changes in risk of exposure, particularly for vulnerable children and older adults. OBJECTIVES: This study quantifies future populations potentially exposed to inland flooding and wildfire smoke under two climate scenarios, highlighting the populations in particularly vulnerable age groups ([Formula: see text] and [Formula: see text]). METHODS: Spatially explicit projections of inland flooding and wildfire under two representative concentration pathways (RCP8.5 and RCP4.5) are integrated with static (2010) and dynamic (2050 and 2090) age-stratified projections of future contiguous U.S. populations at the county level. RESULTS: In both 2050 and 2090, an additional one-third of the population will live in areas affected by larger and more frequent inland flooding under RCP8.5 than under RCP4.5. Approximately 15 million children and 25 million older adults could avoid this increased risk of flood exposure each year by 2090 under a moderate mitigation scenario (RCP4.5 compared with RCP8.5). We also find reduced exposure to wildfire smoke under the moderate mitigation scenario. Nearly 1 million young children and 1.7 million older adults would avoid exposure to wildfire smoke each year under RCP4.5 than under RCP8.5 by the end of the century. CONCLUSIONS: By integrating climate-driven hazard and population projections, newly created county-level exposure maps identify locations of potential significant future public health risk. These potential exposure results can help inform actions to prevent and prepare for associated future adverse health outcomes, particularly for vulnerable children and older adults. https://doi.org/10.1289/EHP2594